Initiation and Development of Spikelets and Florets in Wheat as Influenced by Shading and Nitrogen Supply at the Spikelet Phase - Masanori Toyota; Ichiro Tsutsui; Akihito Kusutani; Koh-ichiro Asanuma (Plant Production Science, 2001)
The spike of the main culm in winter wheat was examined by scanning electron microscopy from the double ridge to 6 days after the terminal spikelet stage to quantitatively evaluate the effects of shading and nitrogen supply at the spikelet phase on the numbers of spikelets and floret primordia, and the development of florets. Positional differences on a spike in grain setting at maturity were also investigated. Nitrogen supply affected neither the rate nor duration of spikelet initiation, the number of spikelets remaining unchanged. Although nitrogen supply positively affected the initiation and development of florets, it slightly reduced the grain weight per spike at maturity due to a decrease in the number of grains per spike and the reduced grain weight. These results suggested that under the field condition, nitrogen supply at the double ridge stage is too late to have a significant effect on the spikelet number, and might induce competition for nitrogen between the main culm and tillers, or induce mutual shading between plants, resulting in lighter grain weight per spike. Shading decreased the rate of spikelet initiation, resulting in a significant decrease in spikelet number. The initiation and the development of florets were also decreased by shading. Lower non -structural carbohydrate content at the terminal spikelet stage suggested that the limited assimilate supply by shading was likely responsible for the decreases in the initiation and development of spikelets and florets.